Contemporary Trends in Utilization of Rescue Intracranial Stenting During Mechanical Thrombectomy in Patients With Stroke in the United States - Fadar Oliver Otite; Smit Patel; Haydn Hoffman; Ameer Hassan; Dileep Yavagal; Amit Singla; Priyank Khandelwal (Stroke: Vascular and Interventional Neurology)
Background Rescue intracranial stenting (RICS) is increasingly recognized as a potentially effective rescue strategy following failed mechanical thrombectomy (MT) for large vessel occlusion due to intracranial atherosclerosis, but population‐level data on contemporary patterns of RICS utilization in MT are lacking. The aim of this study is to describe trends in the utilization of RICS in MT in the United States in the last decade. Methods We conducted a serial cross‐sectional study using all primary acute ischemic stroke (AIS) admissions with MT in the 2010–2020 National Inpatient Sample. RICS admissions were defined as those with procedural codes for “percutaneous insertion of intracranial vascular stent” on same day as MT. We used joinpoint regression to evaluate trends in RICS over time and utilized multivariable‐adjusted regression to compare odds of in‐hospital mortality and routine home discharge between RICS versus non‐RICS admissions over time. Results Of the 5 190 148 primary AIS admissions in the United States across the study period, 3.0% had codes for MT. The proportion of MT admissions increased by over 8‐fold from 0.8% in 2010 to 6.5% in 2020. RICS was utilized in 1.8% of MT admissions but this proportion declined by 5.4% annually (annualized percentage change [APC] −5.4% [95% CI, −7.7% to −3.1%]). However, as a proportion of all AIS admissions, RICS in all AIS increased by 20.5% annually (APC 20.5%, [95% CI, 16.0%–25.2%]). Odds of in‐hospital mortality did not differ between RICS compared to non‐RICS MT admissions (odds ratio 1.39 [95% CI, 0.83–2.32]) but RICS admissions had 50% lower odds of routine home discharge compared with non‐RICS admissions. Conclusion RICS is utilized in just under 2% of MT admissions in the United States. This proportion has declined over time but because of increased MT usage in AIS over time, overall utilization in AIS has increased exponentially over time.